Characterisation of pathogenesis-related genes and resistance gene candidates in banana (Musa acuminata) and their expression during host-pathogen interaction - Yang, Chee Yong; Hamid, Sathyapriya; Wong, Mui Yun (Universiti Putra Malaysia Press, 2016)
Amplified chitinase gene sequence shared 99% homology with Musa acuminata class III acidic chitinase and beta-1,3-glucanase gene sequence was 100% homologous to Musa x paradisiaca beta-1,3-glucanase. Three nucleotide-binding sites and the leucine-rich repeat (NBS-LRR) type of putative RGCs and one serine/threonine kinase gene were characterised at the amino acid level. Kinase-2 (LVLDDVW) and kinase-3 (GSRIIITTRD) motifs in the nucleotide-binding domain were highly conserved in RGC2 and RGC3 and these genes belong to the non-TIR-NBS class RGCs. RGC1 was also clustered into non-TIR-NBS class RGCs; however, many residue substitutions were present in the kinase-2 and kinase-3 motifs. The sub-domain IX (LTEKSDVYSFGVVL) of serine/threonine protein kinase was highly conserved in RGC5 and it shared highest homology with PTH-2 from muskmelon. RT-PCR analysis revealed the differential expression of PR and RGC genes exhibited by different banana genotypes over sampling time. Chitinase was expressed during banana- FocR4 interaction in all three banana genotypes. However, its expression was high and constant in Rastali Mutiara during banana-FocR4 interaction and resulted in very low disease severity in FocR4 inoculated plants (2%) compared to Rastali wild-type (16%) and Jari Buaya (8%) at six weeks after inoculation. This suggests that chitinase may play an important role in disease resistance against FocR4. Besides, our study also shows that Rastali Mutiara can be a potential source of disease-resistant genes for molecular breeding of banana.